A relação com o saber de adolescente em cumprimento de medida socioeducativa no estado de Sergipe: aluno/interno e suas histórias com o “aprender/não aprender” - Dantas, Viviane Andrade de Oliveira (2020)
This thesis aims to analyze how the relationship of adolescents in compliance with a socioeducational measure of hospitalization with knowledge is established. Having as theoretical source the Relation to Knowledge (RS), in what refers specifically to the theory developed by Bernard Charlot. The participants of this research are adolescents who are fulfilling a socio-educational measure of hospitalization at the Centro de Atendimento ao Menor – CENAM/State of Sergipe. The school history of these adolescents faces difficulties at school; consequently, the researcher's interest was to study the relationship of these adolescents with knowledge when faced with what we can call school failure, with the difficulties in learning at school, with the non-appropriation of knowledge, with the sense and the desire to learn. Knowing the life history / singular stories of these adolescents and the relationship they establish with knowledge was the first step to understand the dimensions that affect the meanings these subjects attribute to education, school and knowledge, working on the epistemic, identity relationship and social. Based on this assumption, the guiding question of this research is considered: what is the relationship that adolescents in compliance with a socio-educational hospitalization measure establish with knowledge. To answer this question, the investigation had four bases of support: the relation to the school (meaning, desire); the relation to learning in the family (the first contact); the relation to learning on the street (neighborhood) and; the relation to the intramural school (current situation of adolescent deprivation of liberty). To answer the questions that mobilized this research, we have constituted a methodology appropriate to the work questions and the situation investigated. Therefore, we used the qualitative approach, using field research as a methodological procedure and had CENAM as its locus, which serves male adolescents fulfilling a socio-educational measure of deprivation of liberty. The data obtained were classified into theoretical categories, empirical categories and units of analysis. In the course of this study, we used interviews, balances of knowledge, observation as instruments for data collection and production. This methodological perspective allowed to structure the investigation and data analysis. At CENAM, adolescents are inserted in formal education through the Youth and Adult Education (EJA) modality, which is carried out in partnership with the State Department of Education. In this case, for a better understanding and delimitation of the object of study, 20 (twenty) adolescents (students / interns) who were in the 6th year and enrolled in EJAEF II - 1st stage, were researched. With this, the research demonstrated that the school for students / interns is an important learning space, and it became necessary to demonstrate that they move away from the school when they are involved with violations of social norms - those who still remain, are not fact concentrated on school intellectual activities. The research showed that, for students / interns, respect is learned in the family and results, for them, the most important institution. With regard to learning on the street / in the neighborhood, this becomes a “dangerous” space, which causes poor learning, being associated with criminality.